Mesoporous Silica Nanoparticle Grafted Polypropylene Membrane toward Long‐Term Efficient Oxygenation - Aoxing Feng; Yakai Lin; Dayin Sun; Fangyu Wu; Huanhuan Wu; Yuanhui Tang; Fanchen Zhang; Wei Jia; Lixin Yu; Xiaolin Wang; Zhenzhong Yang (Small Structures)
The trade‐off between gas permeability and resistance to plasma leakage imposes a great challenge for the practical use of membranes in extracorporeal membrane oxygenation (ECMO). Herein, a polypropylene (PP) hollow‐fiber composite membrane is fabricated by simply grafting mesoporous silica nanoparticles onto the commercial PP membrane, which shows a significantly enhanced gas permeability and superior resistance to plasma leakage. The performance metrics such as gas permeability, bubble point, surface hydrophobicity, and plasma leakage resistance are largely influenced by the type of functional groups on the silica nanoparticles (hydroxyl, vinyl, or trifluoropropyl). It is shown that the trifluoropropyl‐group functionalized mesoporous silica nanoparticle grafted composite membrane demonstrates a superior performance than the commercial ECMO membrane of poly(4‐methyl‐1‐pentene) (PMP). The bubble point is greatly elevated from 0.36 to 1.20 MPa while the decrease in gas flux is negligible within 4%. And the leakage resistance time is significantly prolonged from 600 to 4140 min. The gained benefits are originated from the enhanced mass transfer area and diminished surface pores of the composite membrane are grafted with the mesoporous nanoparticles. The high‐performance PP‐based composite membranes are cost‐effective and promising in practical applications of ECMO.